A Transparent broadband all-dielectric water-based metamaterial absorber based on laser cutting. (1st May 2023) - Li, Lintao; Wen, Jingda; Wang, Yichen; Jin, Yue; Wen, Yongzheng; Sun, Jingbo; Zhao, Qian; Li, Bo; Zhou, Ji
Abstract: Gradually attracting attention on the all-dielectric broadband metamaterial absorber is developing in the application of multi-functionalization, such as the optical transparent transmission function of the microwave absorber. In this paper, we designed an all-dielectric transparent broadband metamaterial absorber utilizing the composited structure of the layered and cylindrical water with the shell of cross-shaped PMMA. Then, the series of the patterned shell are fabricated by the two-dimensional laser cutting technology with ultra-fast, accurate, and simplified process. Both the simulated and experimental performance show high absorption over 90% at 13.3–40 GHz and optical transmittance of 73% with polarization insensitivity and wide-angle incident tolerance. Furthermore, the transparent absorber can modulate the low-frequency absorptivity by adjusting the temperature and ion concentration. Our all-dielectric transparent broadband metamaterial absorber based on laser cutting technology has promising potential in a wider range of both civil and military applications.